2018
DOI: 10.1146/annurev-neuro-080317-062007
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression, and Decision Making: A Computational Perspective

Abstract: In everyday life, the outcomes of our actions are rarely certain. Further, we often lack the information needed to precisely estimate the probability and value of potential outcomes as well as how much effort will be required by the courses of action under consideration. Under such conditions of uncertainty, individual differences in the estimation and weighting of these variables, and in reliance on model-free versus model-based decision making, have the potential to strongly influence our behavior. Both anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
178
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(201 citation statements)
references
References 94 publications
(109 reference statements)
17
178
3
3
Order By: Relevance
“…Despite our relatively powerful approach that simultaneously assessed learning and post-learning performance, as well as reward and punishment learning in the context of a within-subject anxiety induction, and contrary to some previous studies, our experiments failed to reveal clear and specific effects of anxiety on learning per se. While surprising at first glance, our null results agree with findings from a small-scale review that shows little to no effects of anxiety on learning and post-learning performance on average and they add to recent results, which have started to challenge the role of anxiety in experience-based decision-making (Bishop and Gagne, 2018;Gillan et al, 2019). A.…”
Section: Resultssupporting
confidence: 88%
“…Despite our relatively powerful approach that simultaneously assessed learning and post-learning performance, as well as reward and punishment learning in the context of a within-subject anxiety induction, and contrary to some previous studies, our experiments failed to reveal clear and specific effects of anxiety on learning per se. While surprising at first glance, our null results agree with findings from a small-scale review that shows little to no effects of anxiety on learning and post-learning performance on average and they add to recent results, which have started to challenge the role of anxiety in experience-based decision-making (Bishop and Gagne, 2018;Gillan et al, 2019). A.…”
Section: Resultssupporting
confidence: 88%
“…Aberrant anticipatory responding to upcoming uncertain threats has been proposed to be a common explanation of anxious states in healthy individuals and anxiety disorders alike (Grupe and Nitschke, 2013). Accordingly, our findings that anxiety leads to changes in informational and environmental uncertainty could prove relevant for understanding the alterations in decision-making and learning observed in anxiety disorders (Bishop and Gagne, 2018;Browning et al, 2015;de Visser et al, 2010;Huang et al, 2017;Miu et al, 2008).…”
Section: States Of Anxiety Bias Computations Of Different Types Of Unsupporting
confidence: 55%
“…Less understood is how temporary states of anxiety in healthy subjects interfere with optimal learning and belief updating in the brain. Identifying the computations that subserve learning under state anxiety is important due to the prevalence of highly anxious states in most real-world environments that are filled with uncertainty (Bach et al, 2011;Bishop and Gagne, 2018). In addition, these insights could expand our understanding of the mechanisms by which anxiety biases beliefs about the world, linking to anxiety-related disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although anxious and depressive behaviors are usually comorbid [30], there are distinct characteristics in these two symptoms. Sonia and colleagues found that individuals with anxiety tend to avoid threat, whereas depression may be mostly identified as decreased pursuit of reward [31]. Considering the different changes in BDNF in stress-related (decreased BDNF in hippocampus) and reward-related systems (increased BDNF in VTA and NAc), stress-induced anxiety and depression may be associated with the degree of activation of different pathways.…”
Section: Bdnf Expression and Mood-related Brain Regionsmentioning
confidence: 99%